Natural disasters and develoment - Toyomane, Norimichi; Yoshida, Shuji; Katsurada, Toshisada (Japan : International Development Center of Japan, 1991)
The book on the impact of natural disasters is particularly severe in developing countries.
Includes bibliographical references.
gau 31/10/2016
Ref
Keywords: Social effect